PEMANFAATAN TEKNOLOGI AUGMENTED REALITY (AR) PADA MUSEUM BETAWI, SETU BABAKAN: The Use of Augmented Reality (AR) Technology at the Betawi Museum, Setu Babakan - Bramantio Aninditho Devalentsky Mayangkoro; Elda Franzia Jasjfi (Universitas Trisakti, 2025)
The Use of Augmented Reality (AR) Technology at the Betawi Museum, Setu Babakan. The development of digital technology, especially Augmented Reality (AR), has opened up new opportunities in the world of education and cultural preservation, including in the museum environment. This study aims to analyze the use of AR technology in the Betawi Museum infographics, Setu Babakan, to increase visitor engagement and enrich understanding of Betawi culture. The study used a qualitative approach with observation, interview, and visual documentation methods, and was supported by literature studies as secondary data. The results of the analysis show that AR at the Betawi Museum provides a more immersive and interactive educational experience, with two main forms, namely 3D audiovisual visualization and interactive infographics. Although there are still some technical obstacles such as limitations in visual design, lighting, and internet connection. In conclusion, the application of AR at the Betawi Museum is a strategic step in transforming traditional museums into more digital, dynamic, and inclusive cultural learning spaces.